LIGHTING DESIGN FOR THE AGING EYES - Kunduraci, Arzu Cilasun (MATTER: International Journal of Science and Technology, 2017)
Lighting allows users to accomplish their tasks, feel safe and understand the surrounding environment. Therefore, it is an inseparable component of buildings. Building codes, energy standards and regulations determine the required illuminances to provide visual comfort. However, the existing requirements are constituted considering healthy eyes only. Different visual comfort requirements for people with visual disabilities, in particular for elderly people, are not clear. The world’s older population continues to grow remarkably. In fact, the illuminance requirements show great difference for elderly people. For instance, an average 60 years old eye requires three times more illuminance than an average 20 years old eye. Therefore, a lighting design that complies with the regulations may not satisfy elderly users’ needs.Elderly spend most of their time indoors thus indoor spaces should fulfill their needs. Indoor lighting design and visual comfort are vital to prevent accidents and falls. Though such technical information is critical, it has not sufficiently covered in literature from elderly users’ perspective. For that reason within this study, technical lighting design recommendations for residential areas from previous research have been offered to obtain visual comfort for elderly users. Different visual requirements of each space type are emphasized to promote accessible design for elderly. The research aims to contribute to literature and guide future research on elderly indoor comfort.